STATISTICAL ANALYSIS OF TRENDS IN THE DEVELOPMENT OF THE SERVICE SECTOR IN UZBEKISTAN (World Economics and Finance Bulletin, 2025)
Opinions and comments on the content, nature and history of development of service industries is presented in the article. At the same time, the role of the service sector in the development of the economy of Uzbekistan and the trends of its structural indicators have been determined. In addition, the study of the factors affecting them, the assessment of structural changes, and the volume of services per capita have been determined. Also, the future forecast values of the volume of services per capita were calculated, and conclusions and suggestions were made based on them.